The acquisition of complex morphology insights from Murrinhpatha - Forshaw, William (Trends in language acquisition research ;, 2021)
"Many theories of language acquisition struggle to account for the morphological complexity and diversity of the world's languages. This book examines the acquisition of complex morphology of Murrinhpatha, a polysynthetic language of Northern Australia. It considers semi-naturalistic data from five children (1;9-6;1) collected over a two-year period. Analysis of the Murrinhpatha data is focused on the acquisition of polysynthetic verb constructions, large irregular inflectional paradigms, and bipartite stem verbs, which all pose interesting challenges to the learner, as well as to theories of language acquisition. The book argues that morphological complexity, which broadly includes factors such as transparency, predictability/regularity, richness, type/token frequency and productivity, must become central to our understanding of morphological acquisition. It seeks to understand how acquisition is impacted by differences in morphological systems and by the ways in which children and their interlocutors use these systems"--